The Formation of Social-Religious Attitudes Through the Implementation of Collaborative Learning Models in Islamic Religious Education - Ali Akbar (Sufiya Journal of Islamic Studies, 2024)
This study aims to examine the formation of students' socio-religious attitudes through the application of collaborative learning models in Islamic Religious Education. Socio-religious attitudes are an important foundation in forming students' characters that are balanced between spiritual and social aspects. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation at the junior high school level. The findings show that the instillation of students' socio-religious values ​​can be realized effectively through the integration of aspects of faith, worship, morals, and complementary learning media. The collaborative learning model encourages active involvement of students in the inclusive learning process, and allows for real internalization of values ​​in everyday life. Thus, religious education that combines the three main pillars of religion and is supported by appropriate learning media is able to form students' religious awareness that is not only personal, but also has an impact on their social behavior.